Rolling Barrier Guardrail System - Sunil Thakare, Dr. Satish S. Deshmukh, Kiran Ghorpade, Abhishek Shirle (Mathematical Statistician and Engineering Applications, 2022)
Road accidents pose a significant global challenge, resulting in countless fatalities, injuries, and economic losses each year. The Pune-Mumbai Highway in India, known for its high traffic volume and diverse road conditions, presents a compelling case study to investigate road accident prevention techniques. This review paper aims to critically analyze existing prevention strategies and interventions employed on the Pune-Mumbai Highway to enhance road safety and mitigate accident risks. The paper begins by providing an overview of the current state of road accidents and their consequences worldwide. It then narrows down the focus to the specific context of the Pune-Mumbai Highway, highlighting its characteristics, traffic patterns, and accident statistics. By examining available literature, research studies, and official reports, the paper presents a comprehensive evaluation of various prevention techniques employed on this highway. The review encompasses multiple dimensions of road accident prevention, including engineering measures, enforcement strategies, and educational initiatives. It explores the effectiveness of physical interventions such as road design improvements, traffic control systems, signage, and speed management techniques. Additionally, it evaluates the enforcement mechanisms in place, such as traffic regulations, law enforcement efforts, and penalties. The paper also examines educational campaigns, driver training programs, and public awareness initiatives to assess their impact on behavior change and road safety culture. Based on the analysis of the existing prevention techniques on the Pune-Mumbai Highway, the paper identifies strengths, weaknesses, and potential areas for improvement. It highlights successful interventions that have proven effective in reducing accident rates and suggests recommendations for further enhancing road safety. The findings of this review paper can serve as a valuable resource for policymakers, transportation authorities, and researchers in formulating evidence-based strategies to prevent road accidents on the Pune-Mumbai Highway and similar road networks.